The effect of hydrogen bonding on the excited-state proton transfer in 2-(2′-hydroxyphenyl)benzothiazole: A TDDFT molecular dynamics study - Kungwan N. (2014)
The dynamics of the excited-state proton transfer (ESPT) in a cluster of 2-(2′-hydroxyphenyl)benzothiazole (HBT) and hydrogen-bonded water molecules was investigated by means of quantum chemical simulations. Two different enol ground-state structures of HBT interacting with the water cluster were chosen as initial structures for the excited-state dynamics: (i) an intramolecular hydrogen-bonded structure of HBT and (ii) a cluster where the intramolecular hydrogen bond in HBT is broken by intermolecular interactions with water molecules. On-the-fly dynamics simulations using time-dependent density functional theory show that after photoexcitation to the S 1 state the ESPT pathway leading to the keto form strongly depends on the initial ground state structure of the HBT-water cluster. In the intramolecular hydrogen-bonded structures direct excited-state proton transfer is observed within 18 fs, which is a factor two faster than proton transfer in HBT computed for the gas phase. Intermolecular bonded HBT complexes show a complex pattern of excited-state proton transfer involving several distinct mechanisms. In the main process the tautomerization proceeds via a triple proton transfer through the water network with an average proton transfer time of approximately 120 fs. Due to the lack of the stabilizing hydrogen bond, intermolecular hydrogen-bonded structures have a significant degree of interring twisting already in the ground state. During the excited state dynamics, the twist tends to quickly increase indicating that internal conversion to the electronic ground state should take place at the sub-picosecond scale. © 2012 the Owner Societies.